Effects of day-to-day variation of Opisthorchis viverrini antigen in urine on the accuracy of diagnosing opisthorchiasis in Northeast Thailand - Worasith, Chanika; Wongphutorn, Phattharaphon; Homwong, Chutima; Kopolrat, Kulthida Y.; Techasen, Anchalee; Thanan, Raynoo; Eamudomkarn, Chatanun; Wangboon, Chompunoot; Khuntikeo, Narong; Loilome, Watcharin; Sithithaworn, Jiraporn; Crellen, Thomas; et al. (PLOS ONE, 2022)
Antigen detection in urine using an enzyme-linked immunosorbent assay (ELISA) is more sensitive than fecal examination for diagnosis of opisthorchiasis and for assessment of the effects of drug treatment. It is not known whether day-to-day variation of urine composition, including levels of Opisthorchis viverrini antigen, influences the urine assay. We investigated this topic with the cooperation of participants from two localities in Northeast Thailand. Project participants were screened for parasite infections for three consecutive days using the quantitative formalin-ethyl acetate concentration technique (FECT) to detect O. viverrini eggs and the urine ELISA for detection of O. viverrini antigen. A subset of participants (n = 801) with matched fecal and urine samples were analyzed for comparison of inter-day prevalence estimates and the performance of the urine assay compared against FECT for diagnosis of opisthorchiasis. The daily prevalence measured by the urine assay ranged between 29.0%-30.2% while those by FECT ranged between 11.9%-20.2%. The cumulative three-day prevalence estimate determined by the urine antigen assay was 30.3%, which was significantly higher than that by FECT (20.2%, p < 0.05). A significant positive correlation was found between the concentration of antigen in urine and fecal egg counts (p < 0.001). Overall, the urine assay had better diagnostic performance for opisthorchiasis than fecal examination by FECT. The high sensitivity plus negligible daily variation of O. viverrini antigen in urine indicates the utility of the urine assay for diagnosis, as well as population screening, of opisthorchiasis.